Shift - Bradbury, Jennifer (Jennifer A.) (New York : Atheneum Books for Young Readers, 2008)
When best friends Chris and Win go on a cross country bicycle trek the summer after graduating and only one returns, the FBI wants to know what happened.
Keywords: Bicycles and bicycling -- Fiction; Travel -- Fiction; Missing persons -- Fiction; Best friends -- Fiction; Friendship -- Fiction